The CALO Meeting Assistant System - Tur, Gokhan; Stolcke, Andreas; Voss, Lynn; Peters, Stanley; Hakkani-Tür, Dilek; Dowding, John; Favre, Benoit; Fernández, Raquel; Frampton, Matthew; Frandsen, Mike; Frederickson, Clint; Graciarena, Martin; et al. (IEEE Transactions on Audio, Speech, and Language Processing, 2010)
The CALO Meeting Assistant (MA) provides for distributed meeting capture, annotation, automatic transcription and semantic analysis of multiparty meetings, and is part of the larger CALO personal assistant system. This paper presents the CALO-MA architecture and its speech recognition and understanding components, which include real-time and offline speech transcription, dialog act segmentation and tagging, topic identification and segmentation, question-answer pair identification, action item recognition, decision extraction, and summarization.